Visual impairment in children due to damage to the brain - Dutton, Gordon; Bax, Martin (Clinics in developmental medicine ;, 2010)
Cerebral visual impairment is the most common cause of visual impairment in the developed world. This book describes function, disfunction and management strategies for clinicians.